Improvement in cucurbits for drought and heat stress tolerance — a review (Current Horticulture, 2024)
Cucurbits are sensitive to environmental extremes, and thus high temperature and limited soil moisture are major causes of low yield in hot arid region and will be further magnified by climate change. Some abiotic stresses directly reduce growth, while others affect development in a way that reduces or eliminates the crop's value. The response of plants to environmental stresses depends on developmental stages and length and severity of the stress. Plants may respond similarly to avoid one or more stresses through morphological or biochemical mechanisms. Plant breeders need to translate these findings into stress-tolerant varieties by using all tools available that include germplasm screening, marker-assisted selection and genetic transformation besides conventional breeding methods. Therefore, breeding is one of the most efficient approaches for managing abiotic stresses. The genetically complex responses to abiotic stresses are multigenic and thus more difficult to control and engineer. Several abiotic stress tolerant varieties have been developed utilizing conventional breeding approaches. However, rapid progress is required to reduce the gap between potential yield and actual yield in abiotic stress prone environments. Thus, there is an urgent need of breeding climate-smart varieties of cucurbits tolerance to abiotic stresses which have great potential for meeting increased demand. Keeping in view, an attempt has been made to compile the scattered information on concepts, mechanisms and breeding approaches of abiotic stress tolerance in cucurbits.
Keywords: Abiotic stresses; Breeding approaches; Cucurbits; Drought stress; Heat stress